An interpretative model from the elasticity theory to explore knowledge integration in new product development. Issue 4 (November 2016) - Corallo, Angelo; Lazoi, Mariangela; Secundo, Giustina; DePaolis, Paolo
Abstract This paper presents a conceptual model to explore the knowledge integration (KI) practices of internal and external company actors involved in the New Product Development (NPD) process of the aerospace industry. The model is based on the linkage of elasticity principles, particularly Hooke's Law, to Knowledge Management theory. KI practices are considered as a force pushing the NPD process and are metaphorically described as the spring addressed by Hooke's law. The integration of the knowledge of internal and external company actors impacts NPD, reducing the dimensions of the whole process, in terms of phases, through the application of the concurrent engineering approach. The whole NPD process is improved in terms of the reduction of uncertainty and complexity, and with an 'integrated energy' that sustains the pressure of the fast-changing competitive environment. The model is explored to provide an interpretation of the conceptualisation phase of a new aerospace product development process. Qualitative data were collected and analysed. Insights regarding the applications of the model and the theoretical implications are also provided for applications in other industries.